PENGARUH WARNA KASA PENUTUP AUTOCIDAL OVITRAP TERHADAP JLMLAH JENTIK NYAMUK AEDES AEGYPTI YANG TERTANGKAP - Joko Santoso; Retno Hestiningsih; Ratih Sari Wardani; Sayono - (Jurnal Kesehatan Masyarakat Indonesia, 2007)
Background: Aedes aegypti mosquito is one of the vectors which is able to infect Dengue Hemoryhagic Fever disease mechanically. The examination offree rate of mosquito lat-va in Putwotladi ttist-rict, Grobogai rege,cy,is amounting 86 o/o. One of the techniques to control the population of Aedes aegypti mechaiicallll i, iy installing autocidal ovitrap simply and economically. objective of the research is ti inow the effect i1 ,ori, gauze color autocidal ovitrap on the number of Aedes Aegypti lar-vie which are trappetl. Type of ie resiarch is explanatory research by using experimental research design with post-test only tlisrgn approach. The researchsubject is conductecl in the surroundings of Purwodacti dtitrict seitlement *tti olrrr"e repetition. The measured variable consists of cover gauze color autocidal ovitrap antl the number of Aetles Aegtpti lat-vae which aretrapped. Collected data are analyzed with statistical test of one-way anovct rutth srgnifiilit level 5,%. Result of the research is that the numbers of Aedes aegtpti lar-vae, which ari trapped nrrr,:rliig to the categoD,of covet. gat:ze color autocidal ovitrap, are l9 black-colored larvae, l7 pink-cotored larvae, l2 white-colot-ed larttae, and S light blue-colored larvae. Result of the study of one-way inova is p:0, 5gg. In conclusion, there is noeffect of cover gauze color autocidal ovitrap on the number of Aecles aegypti larvee which are trappecl.Keywords : cover color, autocidal ovitrap, larvae, Aedes aegypti